2021
DOI: 10.3122/jabfm.2021.02.200396
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Preferences for Health Care Chaplaincy Services Among US Adults

Abstract: Health care chaplains intervene on unmet religious/spiritual (R/S) needs in health care settings that are associated with poor outcomes. Little is known about demand for their services. The purpose of this study was to describe population-level awareness and perceptions of health care chaplains and preferences for their services.Methods: Data came from a cross-sectional survey of a nationally representative sample of US adults ≥ 18 years of age (n = 1020). Participants were asked about preferences for chaplain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Our survey tracks with both of these in terms of patients' overall interest in spiritual care, but diverges in the details. We find a clinic population that is generally open to overt religiosity such as prayer (like Piderman et al, 2010); at the same time, our patients with high religiosity report greater desire for help with secular topics (more like Rajaee & Patel, 2021). These nuances may be regional, or may reflect the additional value of assessing patients' public and private religiosity in considering their pastoral care needs.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Our survey tracks with both of these in terms of patients' overall interest in spiritual care, but diverges in the details. We find a clinic population that is generally open to overt religiosity such as prayer (like Piderman et al, 2010); at the same time, our patients with high religiosity report greater desire for help with secular topics (more like Rajaee & Patel, 2021). These nuances may be regional, or may reflect the additional value of assessing patients' public and private religiosity in considering their pastoral care needs.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, Piderman et al (2010), measuring mostly overtly religious individuals, found that nearly 70% of their respondents desired chaplain care, and the mostly highly endorsed reason for wanting to see a chaplain was “to be reminded of God's care and presence” followed by “prayer or scripture study.” Our survey tracks with both of these in terms of patients’ overall interest in spiritual care, but diverges in the details. We find a clinic population that is generally open to overt religiosity such as prayer (like Piderman et al, 2010); at the same time, our patients with high religiosity report greater desire for help with secular topics (more like Rajaee & Patel, 2021). These nuances may be regional, or may reflect the additional value of assessing patients’ public and private religiosity in considering their pastoral care needs.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Therefore, one way to ensure there is a focus on meaning-making is to offer mindfulness-based interventions (and mind-body interventions more broadly). In addition, existential anxiety could more explicitly be targeted through meaning-centered therapy (Masterson-Duva et al, 2020), logotherapy (Liu et al, 2021), and chaplaincy services (Rajaee & Patel, 2021). The adoption of system-based stepped and collaborative care approaches (Maehder et al, 2019) that initially focus on less-intensive treatments (e.g., patient education), and then "step up" patients to more intensive treatments (e.g., yoga for PTSD) based on initial treatment response could lessen the burden on healthcare systems that would likely occur when new types of services (e.g., meaning-centered therapy) are added.…”
Section: Future Directionsmentioning
confidence: 99%